PENGARUH METODE POSTER COMMENT PADA MATERI SISTEM GERAK TERHADAP HASIL BELAJAR SISWA KELAS XI MIA MAN 1 LANGSA - Balqis, Putri; Elfrida, Elfrida; Atmaja, Teuku Hadi Wibowo (FKIP Universitas Tanjungpura, 2026)
Poster comment is an active learning approach that aims to improve students' critical thinking skills and involve them in solving problems using the images presented. This study aims to analyze the impact of the poster comment method on students in class XI MIA at MAN 1 Langsa. The method applied in this study is a quasi-experimental. The research design used is Pretest-posttest control group design, which involved two classes, namely the experimental class and the control class. The number of samples in this study consisted of 30 students in the experimental class and 30 students in the control class. The research instrument used was 20 multiple-choice questions. The results showed that the average score of students in the experimental class reached 75, while in the control class it was only 60. Hypothesis testing shows that the t count value is 6,065 and the t table value is 2,048 with a significance level of 0,05 (5%), so that t count > t table is accepted. Thus, it can be concluded that the application of the poster comment method on the material of the motion system has an effect on the learning achievement of class XI MIA students at MAN 1 Langsa.